Autonomic Nerve Regulation of Colonic Peristalsis in Guinea Pigs - Gribovskaja-Rupp, Irena (Korean Society of Neurogastroenterology and Motility, 2014)
BACKGROUND/AIMS: Colonic peristalsis is mainly regulated via intrinsic neurons in guinea pigs. However, autonomic regulation of colonic motility is poorly understood. We explored a guinea pig model for the study of extrinsic nerve effects on the distal colon. METHODS: Guinea pigs were sacrificed, their distal colons isolated, preserving pelvic nerves (PN) and inferior mesenteric ganglia (IMG), and placed in a tissue bath. Fecal pellet propagation was conducted during PN and IMG stimulation at 10 Hz, 0.5 ms and 5 V. Distal colon was connected to a closed circuit system, and colonic motor responses were measured during PN and IMG stimulation. RESULTS: PN stimulation increased pellet velocity to 24.6 ± 0.7 mm/sec (n = 20), while IMG stimulation decreased it to 2.0 ± 0.2 mm/sec (n = 12), compared to controls (13.0 ± 0.7 mm/sec, P < 0.01). In closed circuit experiments, PN stimulation increased the intraluminal pressure, which was abolished by atropine (10(−6) M) and hexamethonium (10(−4) M). PN stimulation reduced the incidence of non-coordinated contractions induced by NG-nitro-L-arginine methyl ester (L-NAME; 10(−4) M). IMG stimulation attenuated intraluminal pressure increase, which was partially reversed by alpha-2 adrenoceptor antagonist (yohimbine; 10(−6) M). CONCLUSIONS: PN and IMG input determine speed of pellet progression and peristaltic reflex of the guinea pig distal colon. The stimulatory effects of PN involve nicotinic, muscarinic and nitrergic pathways. The inhibitory effects of IMG stimulation involve alpha-2 adrenoceptors.